2020
DOI: 10.3390/ijerph17217912
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Social Engagement in Older Adults Based in Lombardy during the COVID-19 Lockdown: The Long-Term Effects of a Course on Social Networking Sites Use

Abstract: Older adults are less familiar with communication technology, which became essential to maintain social contacts during the COVID-19 lockdown. The present study aimed at exploring how older adults, previously trained for Social Networking Sites (SNSs) use, experienced the lockdown period. In the first two weeks of May 2020, telephone surveys were conducted with individuals aged 81–85 years and resident in Abbiategrasso (Milan), who previously participated in a study aimed at evaluating the impact of SNSs use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 40 publications
5
39
0
Order By: Relevance
“…In this situation, social media have become more important for maintaining social contacts [ 27 ]. A clinical trial that trained older adults to use social networking sites found that those who had participated in the training were more likely to use social networking and reported reduced feelings of being left out [ 41 ]. Thus, public health strategies to improve social media and digital communication literacy for older adults in the community may be recommended to reduce social loneliness in the older population.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, social media have become more important for maintaining social contacts [ 27 ]. A clinical trial that trained older adults to use social networking sites found that those who had participated in the training were more likely to use social networking and reported reduced feelings of being left out [ 41 ]. Thus, public health strategies to improve social media and digital communication literacy for older adults in the community may be recommended to reduce social loneliness in the older population.…”
Section: Discussionmentioning
confidence: 99%
“…Study 2 explores the effects of neighborhood identification. Since previous research has shown that neighborhood identification is positively associated with strength of social network (Moyano-Díaz & Mendoza-Llanos, 2021 ), which, in turn, is negatively associated with loneliness (Rolandi et al, 2020 ), these two aspects of social support are included in Study 2.…”
Section: Introductionmentioning
confidence: 99%
“…As seen during the COVID-19 health emergency, these clients are at a greater risk for infection and mortality [ 49 ], and their self-isolation for safety led to psychological and social challenges [ 50 , 51 ]. Therefore, innovative ways to deliver care to such populations has become critical during the COVID-19 lockdowns [ 52 ], including the use of a mix of digital and non-digital services (e.g., telephone, local community workers, etc.) to maintain social connections considered essential [ 53 ] despite the technology barriers [ 54 , 55 ].…”
Section: Research On Aging and Services To Create Valuementioning
confidence: 99%